Application of Organic Liquid Fertilizer on Growth and Production of RiceVarieties (Oryza sativa L.) - Indra K., Hermawan; Ginting, Jonatan; Charloq (Jurnal Online Pertanian Tropik, 2019)
The aims of this study was to determine the effect of organic liquid fertilizer concentration and varieties on the growth and production of several varieties rice. This research had done at Desa Sendang Rejo, Kecamatan Binjai, North Sumatera with the 50 meters of sea level, from August until November 2016. This research used randomized block design with 2 factor treatments. The first factor was organic liquid fertilizer concentration with 4 levels 0 cc/ litre of water, 3 cc/liter of water, 6 cc/ litre of water and 9 cc/liter of water. The second factor was varieties with 3 levels Ciherang, Inpari 30 and Inpari 32. The result showed that the concentration organic liquid fertilizer significantly effect the plant height, tillers, 1000 grain weight and production per plant. Best result is obtained in treatment 9 cc/litre of water.